2011
DOI: 10.1371/journal.pone.0023614
|View full text |Cite
|
Sign up to set email alerts
|

P-glycoprotein Dysfunction Contributes to Hepatic Steatosis and Obesity in Mice

Abstract: Although the main role of P-glycoprotein (Pgp) is to extrude a broad range of xenochemicals and to protect the organism against xenotoxicity, it also transports a large range of endogenous lipids. Using mice lacking Pgp, we have investigated the possible involvement of Pgp in lipid homeostasis in vivo. In a long term study, we have followed the food intake, body status and lipid markers in plasma and liver of wild-type and mdr1ab-/- mice over 35 weeks. Pgp-deficient mice showed excess weight, hypertrophy of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…(abcb1) knock-out mice with a high-fat diet induced obesity (Foucaud-Vignault et al, 2011). Likewise, in humans, a polymorphism of ABCB1 influencing transcription and function is associated with obesity (Ichihara et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…(abcb1) knock-out mice with a high-fat diet induced obesity (Foucaud-Vignault et al, 2011). Likewise, in humans, a polymorphism of ABCB1 influencing transcription and function is associated with obesity (Ichihara et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Among the candidates, multidrug transporter ABCB1, which is located at the apical pole of enterocyte, can act as a cholesterol floppase. 23 We recently showed that older mice deficient for both isoforms of the apical cholesterol floppase ) spontaneously develop hepatic steatosis, obesity, diabetes mellitus, and increased HDL-C. 29 We performed our studies in 15-week-old male mice that presented with similar cholesterol levels ( Figure VIA in the online-only Data Supplement), before metabolic disturbances arise. We observed that ABCB1a/b −/− mice present with 26% less fecal cholesterol excretion (P<0.05; Figure 6A).…”
Section: Abcb1 Contributes To Ticementioning
confidence: 99%
“…In addition to CYPs, pyrethroids may impact mammalian drug transporters, which contribute in a major way to xenobiotic detoxification [22] and are often coordinately regulated with drug metabolizing enzymes [23]. Indeed, activity of P-glycoprotein (P-gp), an ATP-binding cassette (ABC) efflux pump encoded by the multidrug resistance (MDR) 1 gene/ ABCB1 and handling a broad range of amphiphilic cationic drugs as well as various endogenous lipids [24, 25], has been shown to be inhibited by some pyrethroids [26, 27]. The ABC efflux pump breast cancer resistance protein (BCRP/ ABCG2 ) may also interfere with pyrethroids because its ATPase activity is blocked by the pyrethroids permethrin and cypermethrin [28].…”
Section: Introductionmentioning
confidence: 99%